Multispecies and Clonal Dissemination of OXA-48 Carbapenemase in Enterobacteriaceae From Companion Animals in Germany, 2009—2016 - Pulss, Sandra; Stolle, Inka; Stamm, Ivonne; Leidner, Ursula; Heydel, Carsten; Semmler, Torsten; Prenger-Berninghoff, Ellen; Ewers, Christa (Frontiers in Microbiology, 2018)
1 ABSTRACT The increasing spread of carbapenemase-producing Enterobacteriaceae (CPE) poses a serious threat to public health. Recent studies suggested animals as a putative source of such bacteria. We investigated 19,025 Escherichia coli, 1607 Klebsiella spp. and 570 Enterobacter spp. isolated from livestock, companion animal, horse and pet samples between 2009 and 2016 in our routine diagnostic laboratory for reduced susceptibility to carbapenems (CP) by using meropenem-containing media. Actively screened CP non-susceptible strains as well as 367 archived ESBL/AmpC-β-lactamase-producing Enterobacteriaceae were then tested for the presence of CP genes by PCRs. Among 21,569 isolates, OXA-48 could be identified as the sole carbapenemase type in 137 (0.64%) strains. The blaOXA-48 gene was located on a ~60 kb IncL plasmid and sequence analysis revealed high similarity to reference plasmid pOXA-48a, which has been involved in the global spread of the blaOXA-48 gene in humans since many years. K. pneumoniae was the predominant OXA-48 producer (n=86; 6.6% of all K. pneumoniae isolates), followed by E. cloacae (n=28; 5.0%), K. oxytoca (n=1; 0.3%), and E. coli (n=22, 0.1%). OXA-48 was not found in livestock, but in dogs (120/3182; 3.8%), cats (13/792; 1.6%), guinea pig (1/43; 2.3%), rat (1/23; 4.3%), mouse (1/180; 0.6%), and one rabbit (1/144; 0.7%). Genotyping identified few major clones among the different enterobacteria species, including sequence types ST11 and ST15 for K. pneumoniae, ST1196 for E. coli, and ST506 and ST78 for E. cloacae, most of which were previously involved in the dissemination of multidrug-resistant strains in humans. The majority of OXA-48 isolates (n=112) originated from a university veterinary clinic (UVC), while animals from further 16 veterinary institutions were positive. Clonal analyses suggested nosocomial events related to different species and STs in two veterinary clinics and horizontal transfer of the pOXA-48-like plasmid between bacterial species and animals. A systematic monitoring is urgently needed to assess the dissemination of CPE not only in livestock but also in companion animals and veterinary clinics.